PENGARUH PENAMBAHAN GLISEROL TERHADAP SIFAT MEKANIK FILM PLASTIK BIODEGRADASI DARI PATI KULIT SINGKONG - Zulisma Anita; Fauzi Akbar; Hamidah Harahap (Talenta Publisher (Universitas Sumatera Utara), 2013)
Biodegradable plastics are plastics that will decompose in nature with the help of microorganisms. The use of starch as the main material of plastic manufacturing has great potential because in Indonesia there are different starch crops. To obtain bioplastics, starch is added to the glycerol, in order to obtain a more flexible plastic and elastic. This study reviews the use of cassava starch and glycerol skin asa base for the manufacture of biodegradable plastics. The purpose of this research is to know the effect of adding glycerol in the process of making biodegradable plastic from cassava peel waste. In this research, the study of bioplastic manufacturing mixed starch with glycerol as a plastisizer to do variations of the glycerol. The results obtained in the form of a thin sheet of plastic (plastic film) that have been tested mechanical properties obtained optimum data variables namely cassava starch composition 3,5%, and the power og pull 0,02122Mpa, and plastic film storage time for 14 days.